FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING SECARA VOLUNTARY PADA PERUSAHAAN MANUFAKTUR - Alexandros Ngala Solo Wea; Dewi Murdiawati (Jurnal Bisnis dan Ekonomi, 2015)
This study aimed to analyzed the factors that affect voluntary auditor switching on manufacturing companies listed in Indonesia Stock Exchange (IDX). The population in this study are all companies listed in Indonesia Stock Exchange in the period 2009 to 2014. The number of manufacturing firms sampled in this study were 630 companies observations obtained by purposive sampling method. The data analysis technique used is logistic regression analysis with SPSS version 21. Based on the analysis conducted, the results showed that the variables the percentage change in ROA and audit opinion does not affect the size of the sample companies to perform switching auditors, while change of management, financial distress, the public accountant firm’s, the client size having a significant influence on the company sample to perform the auditor switching.Keywords: Change of Management, Financial Distress, Public Accountant Firm’s, the percentage change in ROA, Client’s size, Audit Opinion and Auditor Switching.